Responses of evergreen and deciduous Quercus species to enhanced ozone levels. - Calatayud, Vicent; Cerveró, Júlia; Calvo, Esperanza; García-Breijo, Francisco-José; Reig-Armiñana, José; Sanz, María José (Environmental pollution (Barking, Essex : 1987), 2011)
Plants of one evergreen oak (Quercus ilex) and three deciduous oaks (Q. faginea, with small leaves; Q. pyrenaica and Q. robur, with large leaves) were exposed both to filtered air and to enhanced ozone levels in Open-Top Chambers. Q. faginea and Q. pyrenaica were studied for the first time. Based on visible injury, gas exchange, chlorophyll content and biomass responses, Q. pyrenaica was the most sensitive species, and Q. ilex was the most tolerant, followed by Q. faginea. Functional leaf traits of the species were related to differences in sensitivity, while accumulated ozone flux via stomata (POD1.6) partly contributed to the observed differences. For risk assessment of Mediterranean vegetation, the diversity of responses detected in this study should be taken into account, applying appropriate critical levels.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd accession-num: 20974507
Keywords: Anatomy; Critical levels; Functional leaf traits; Ozone; photosynthesis; Stomatal conductance